A study on the relationship between the learning process with job satisfaction in origin technology (OTSB) / Hasnul Zuhairi Abu Hassan - Abu Hassan, Hasnul Zuhairi (Faculty of Business and Management, 2001)
Process of learning is a process, which is the act, or process of acquiring knowledge or skills. They have four type of learning that the company can adopted or implanted in their company operations which is, the intuitive approach, the incidental approach, retrospective approach and the prospective approach. Concept of learning process is to create skills, acquiring and transferring Knowledge, with learning process, it might help the company employee to have a better and productivity worker in order improve the company operations. Employee satisfaction refers to the individual feeling about something that they have done before. And based on the theorist it's very associated with other positive organizational outcomes. Four items in measured the employee satisfaction is payment, promotion opportunities, relations with other employees and job assignments.